One-year outcomes of infants born with congenital diaphragmatic hernia: a national population cohort study. Issue 6 (1st June 2019) - Long, Anna-May; Bunch, Kathryn J; Knight, Marian; Kurinczuk, Jennifer J; Losty, Paul Damian
Abstract : Objective: To report outcomes to 1 year, in infants born with congenital diaphragmatic hernia (CDH), explore factors associated with infant mortality and examine the relationship between surgical techniques and postoperative morbidity. Design: Prospective national population cohort study. Setting: Paediatric surgical centres in the UK and Ireland. Method: Data were collected to 1 year for infants with CDH live-born between 1 April 2009 to 30 September 2010. Factors associated with infant mortality are explored using logistic regression. Postoperative morbidity following patch versus primary closure, minimally invasive versus open surgery and biological versus synthetic patch material is described. Data are presented as n (%) and median (IQR). Results: Overall known survival to 1 year was 75%, 95% CI 68% to 81% (138/184) and postoperative survival 93%, 95% CI 88% to 97% (138/148). Female sex, antenatal diagnosis, use of vasodilators or inotropes, being small for gestational age, patch repair and use of surfactant were all associated with infant death. Infants undergoing patch repair had a high incidence of postoperative chylothorax (11/54 vs 2/96 in infants undergoing primary closure) and a long length of hospital stay (41 days, IQR 24–68 vs 16 days, IQR 10–25 in primary closure group). Infants managed with synthetic patch material had a high incidence of chylothorax (11/34 vs 0/19 with biological patch). Conclusion: The majority of infant deaths in babies born with CDH occur before surgical correction. Female sex, being born small for gestational age, surfactant use, patch repair and receipt of cardiovascular support were associated with a higher risk of death. The optimum surgical approach, timing of operation and choice of patch material to achieve lowest morbidity warrants further evaluation.